Teacher Professionalism, Teacher Monitoring in Learning from Home, Parental Participation, and Android-Assisted Learning as Predictors of Students Achievement in COVID-19 Pandemic - Donald Samuel Slamet Santosa; Retnowati Retnowati; Slameto Slameto (International Journal of Science and Applied Science: Conference Series, 2020)
During the COVID-19 pandemic, the Indonesian government implements open and distance learning (ODL) for K-12 until December 2020. Home learning is demanded to have similar quality to learning at school. One indicator of the quality of learning is students achievement. Based on a systems approach, this study sought to find predictors of students’ achievement through ODL in which teacher professionalism (input), android-assisted learning, learning monitoring by the teacher, and parental participation (process) were the predictors of students’ learning outcomes (output). The data sources of this study were obtained from 102 teachers of 487 members of Slameto facebook accounts; data netted with a questionnaire of 24 items that were valid and reliable. To analyze the data, the researchers used the Step Wise Model Regression technique assisted by SPSS for Windows version 25. The results showed that teacher professionalism was the main determinant of students’ achievement with a contribution of 31.30% (model 1); when it was accompanied by monitoring of learning by the teacher, it increased to 37.90% (model 2), and when it was accompanied by parental participation, it gained 43.60% contribution (model 3). This study emphasizes the need for a management model based on parental participation in improving the quality of learning from home (ODL).